Articular cartilage repair and the evolving role of regenerative medicine - Pieter K Bos; Marloes L van Melle; Gerjo JVM van Osch (Open Access Surgery, 2010)
Pieter K Bos1, Marloes L van Melle1, Gerjo JVM van Osch1,21Department of Orthopaedic Surgery, Erasmus MC, Rotterdam, the Netherlands; 2Department of Otorhinolaryngology, Erasmus MC, Rotterdam, the NetherlandsAbstract: Among the growing applications of regenerative medicine, clinical articular cartilage repair has now been used for 2 decades and forms a successful example of translational medicine. Cartilage is characterized by a limited intrinsic repair capacity following injury. Articular cartilage defects cause symptoms, are not spontaneously repaired, and are generally believed to result in early osteoarthritis. Marrow stimulation techniques, osteochondral transplantation, and cell-based therapies, such as autologous chondrocyte implantation (ACI) and use of mesenchymal stem cells (MSCs), are used for tissue regeneration, symptom relief, and prevention of further joint degeneration. The exact incidence of cartilage defects and the natural outcome of joints with these lesions are unclear. Currently available cartilage repair techniques are designed for defect treatment in otherwise healthy joints and limbs, mostly in young adults. The natural history studies presented in this review estimated that the prevalence of cartilage lesions in this patient group ranges from 5% to 11%. The background and results from currently available randomized clinical trials of the three mostly used cartilage repair techniques are outlined in this review. Osteochondral transplantation, marrow stimulation, and ACI show improvement of symptoms with an advantage for cell-based techniques, but only a suggestion that risk for joint degeneration can be reduced. MSCs, characterized by their good proliferative capacity and the potential to differentiate into different mesenchymal lineages, form an attractive alternative cell source for cartilage regeneration. Moreover, MSCs provide a regenerative microenvironment by the secretion of bioactive factors. This trophic activity is believed to limit damage and stimulate intrinsic regenerative responses. Finally, important clinical issues are discussed, including techniques to study the role of implanted cells in tissue regeneration using cell labeling and cell tracking, the improvement of cartilage integration, the use of delayed gadolinium-enhanced magnetic resonance imaging of cartilage for early judgment of joint degeneration/regeneration, and the influence of regulatory rules for therapeutic application development.Keywords: articular cartilage, repair, imaging, techniques